Persistence of Schistosoma haematobium transmission and associated risk factors among patients living in Kwara State, North-Central Nigeria after mass drug administration - Sunday, Joseph O.; Oso, Opeyemi G.; Babamale, Abdulkareem O.; Ugbomoiko, Samuel U. (Ceylon journal of science, 2025)
When an infected person urinates in a river, the aquatic environment becomes contaminated. The transmission to additional gullible people who come into contact with such an environment is known as the “ripple effect”. This research examined the interactions between people and their surroundings, evaluating the likelihood, severity, morbidity, and risk factors of infection following the use of mass drug administration. Urine samples from 4,902 subjects were examined for Schistosoma haematobium using parasitological techniques, while semi-structured questionnaires were completed to obtain information on individual biodata and other epidemiological variables influencing transmission. During the preliminary survey, the overall infection prevalence in the studied areas was 15.4%, while one year post treatment, it increased to 30.1% in the selected study areas. In the Edu LGA, post-treatment infection rates in men increased from 46.6% to 53.9%, while those in women rose from 31.4% to 40.2%. Following treatment, the male rate in Patigi LGA fell from 48.7% to 35.9%, while the female rate fell from 44.1% to 28.8%. Age and gender had an impact on prevalence, intensity, and morbidity. Source of water supply (adjusted odds ratio (aOR) = 467.41 and 6.58), family income (aOR = 178.0 and 2.77), occupation (aOR = 4.00 and 1.55) and individual relationship with the head of the family (aOR = 0.14 and 0.67) were common risk factors for infection in Edu and Patigi communities.  Infection was also linked to education (aOR = 4.23) and individual sex (aOR = 1.65) in Edu communities. Given the relatively high prevalence of Schistosoma haematobium in the study area, it is likely that schistosomiasis will continue to be a major public health concern in North Central Nigeria. Government organizations that are relevant should focus on long-term strategies for reducing schistosome infection.